ANALISIS PERENCANAAN PENGELOLAAN KEUANGAN DESA - Muhammad Yusuf; Romandhon Romandhon; Muhammad Elfan Kaukab (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract. This study aims to determine the suitability of village fund management planning in Slukatan Village, Mojotengah District, Wonosobo Regency with village financial management planning according to the Minister of Domestic Affairs Regulation Number 113 of 2014 concerning Village Financial Management. This research is descriptive qualitative research using primary and secondary data collected by observation, interview, and documentation techniques. In this study, the authors analyzed the data by collecting, reducing, and presenting data until it was sufficient to draw conclusions. The validity of the research data was tested using the triangulation method. The result of this research is an analysis of the suitability of village financial management planning according to the Minister of Domestic Affairs Regulation Number 113 of 2014 concerning Village Financial Management. The results of the analysis of the suitability of village financial management planning in Slukatan Village are not yet fully in accordance with the Minister of Domestic Affairs Regulation Number 113 of 2014 concerning Village Financial Management.